Whole-Transcriptome Analysis of Preadipocyte and Adipocyte and Construction of Regulatory Networks to Investigate Lipid Metabolism in Sheep - Xiao, Cheng; Wei, Tian; Liu, Li Xiang; Liu, Jian Qiang; Wang, Chun Xin; Yuan, Zhi Yu; Ma, Hui Hai; Jin, Hai Guo; Zhang, Li Chun; Cao, Yang (Frontiers in Genetics, 2021)
Many local sheep breeds in China have poor meat quality. Increasing intramuscular fat content (IMF) can significantly improve the quality of mutton. However, the molecular mechanisms of intramuscular adipocyte formation and differentiation remain unclear. This study compared differences between preadipocytes and mature adipocytes by whole transcriptome sequencing and constructed systematically regulatory networks according to the relationship predicted among the differentially expressed RNAs (DERs). Sequencing results showed that in this process, there were 1196, 754, 100, and 17 differentially expressed mRNAs, LncRNAs, microRNAs, and circRNAs, respectively. Gene Ontology analysis showed that most DERs enriched in Cell Part, Cellular Process, Biological Regulation, and Binding terms. KEGG analysis found that the DERs primarily focused on Focal adhesion, PI3K-Akt, MAPK, PPAR signaling pathways. 40 DERs were randomly selected from the core regulatory network to verify the accuracy of the sequence data. The results of qPCR showed that the DERs expression trend was consistent with sequence data. Four novel promising candidate miRNAs (miR-336, miR-422, miR-578, miR-722) played crucial roles in adipocyte differentiation, and they also participated in multiple and important regulatory networks. We verified the expression pattern of the miRNAs and related pathways' members at five-time point in adipocyte differentiation process (0, 2, 4, 6, 8, 10 day) by qPCR, it including: miR-336/ACSL4/LncRNA-MSTRG71379/circRNA0002331;miR-422/FOXO4/LncRNA-MSTRG54995/circRNA0000520; miR-578/IGF1/LncRNA-MSTRG102235/circRNA0002971; miR-722/PDK4/LncRNA-MSTRG107440/circRNA0002909. In this study, our data provided plenty of valuable candidate DERs and regulatory networks for researching the molecular mechanisms of sheep adipocyte differentiation and will assist studies in improving the IMF.